Brevibacillus migulae sp. nov., isolated from a Yellow River sediment sample. Issue 11 (15th November 2020) - Niu, Mingming; Ming, Hong; Cheng, Li-jiao; Yi, Bing-fang; Xia, Ting-ting; Li, Meng; Nie, Guo-Xing
Abstract : Strain CFH S0501 T, a novel Gram-stain-positive, aerobic, rod-shaped, endospore-forming and motile micro-organism with peritrichous flagella, was isolated from a sediment sample collected from the Yellow River in Henan Province, PR China. Optimum growth was observed at 28 °C, pH 7.0 and without NaCl. Phylogenetic analysis based on the 16S rRNA gene sequences indicated that the strain belonged to the genus Brevibacillus and was closely related to Brevibacillus centrosporus DSM 8445 T and Brevibacillus ginsengisoli Gsoil 3088 T (with 96.8 and 96.7 % sequence similarity, respectively). The predominant menaquinone was MK-7. Major cellular fatty acids were anteiso-C15 : 0 and iso-C15 : 0 . Polar lipids consisted of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylmonomethylethanolamine, phosphatidylethanolamine, two unidentified phospholipids and an unidentified polar lipid. The cell-wall peptidoglycan was found to contain meso-diaminopimelic acid. The genome size was 5.26 Mbp with a G+C content of 49.7 mol%. The average nucleotide identity (ANI) and in silico DNA–DNAhybridization (DDH) values between CFH S0501 T and the other species of the genus Brevibacillus were found to be low (ANIm <86.11 %, ANIb <70.30 % and DDH <25.00 %). Based on physiological properties, chemotaxonomic characteristics and low ANI and DDH results, strain CFH S0501 T is considered to represent a novel species, for which the name Brevibacillus migulae sp. nov. is proposed. The type strain is CFH S0501 T (=DSM 29940 T =BCRC 80809 T ).